South African industrial training discourse and policy from 1977 to 1982 - Schaffer, Angela Joan (School of Education, 2019)
This study examines the South African industrial training discourse and policy between 1977 and 1982. The period begins with the appointment of the Riekert and Wiehahn Commissions of Inquiry, both of which contributed materially to the restructuring of official discourse and policy affecting black industrial workers. The study ends after the first year of implementation of the Manpower Training Act of 1981. A method of ideological critique is developed and applied to the language and assumptions of the industrial training discourse and policy in order to show how the dominant industrial training ideas were formulated and given public exposure by significant reformist groups within the state and the capitalist class during a period of general ideological, economic and political change and contestation. The historical context is traced in order to situate the emergence of the reformulated and increasingly coherent dominant industrial training discourse. Prominent themes in this discourse such as the 'skills shortage crisis' are examined and related to developments in the South African social formation and economy. The agents and themes of the counter discourses in the industrial training arena are also identified and discussed. Finally, attention is given to the educational meanings which are subsumed within the industrial training formulations and it is shown how general adult education concerns are largely discarded in favour of considerations of capital accumulation in industrial training policy and rhetoric. It is argued that industrial training policy reflects the dual state strategy of incorporation of the relatively privileged sectors of the black population into a deracialized core economy in the metropolitan centres of South Africa and control of the numerically dominant poor Africans. The industrial training legislation and official guidelines for practice stress rigidly planned closed courses for worker-learners with the emphasis falling on positive attitudes towards the free enterprise system, specific and limited 'on-the-line' skills and worker-management harmony. The content of training courses is monitored through the system of training course registration and rewards for approved courses and methods are offered in the form of generous tax incentives.